2023
DOI: 10.1038/s41598-023-31814-2
|View full text |Cite|
|
Sign up to set email alerts
|

Geriatric nutritional risk index as a prognostic marker for patients with upper tract urothelial carcinoma receiving radical nephroureterectomy

Abstract: To investigate the prognostic value of the geriatric nutritional risk index (GNRI) in patients with upper tract urothelial cell carcinoma (UTUC) receiving radical nephroureterectomy (RNU). Between January 2001 and December 2015, we enrolled 488 patients with UTUC underwent RNU in Taichung Veterans General Hospital. GNRI before radical surgery was calculated based on serum albumin level and body mass index. The malnutritional status was defined as GNRI < 92.0. Using Kaplan–Meier analyses and Cox proportional… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Moreover, there are reports assessing GNRI as a prognostic biomarker, encompassing younger patients with cancer, indicating that GNRI is associated with poor prognosis in various malignancies and can be applied not only in elderly patients but also in young patients. [14][15][16][17][18] However, its prognostic utility for patients with HNC has not been consistently demonstrated. Research has reported an association of low GNRI scores with unfavorable survival outcomes in patients with HNC.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there are reports assessing GNRI as a prognostic biomarker, encompassing younger patients with cancer, indicating that GNRI is associated with poor prognosis in various malignancies and can be applied not only in elderly patients but also in young patients. [14][15][16][17][18] However, its prognostic utility for patients with HNC has not been consistently demonstrated. Research has reported an association of low GNRI scores with unfavorable survival outcomes in patients with HNC.…”
Section: Introductionmentioning
confidence: 99%